Simple model for flow field division and flow structure calculation in a vortex tube. (July 2022) - Li, Nian; Jiang, Guannan; Gao, Neng; Chen, Guangming
Highlights: Research idea of dividing the vortex tube flow field into six regions was proposed. An expression for the axial velocity profile was developed. The mathematical model for the flow field based on the axial velocity was established. The flow fields under four different μ c were computed and analyzed. The reliability of the calculation model was verified through experimental data. Abstract: The flow pattern and energy transfer process in the vortex tube are extremely complex, resulting in the difficulty of the direct calculation and prediction of the flow structure and temperature separation performance of a vortex tube. In view of this, research idea of dividing the vortex tube flow field into six regions was proposed, corresponding simplifications were made in different regions according to the flow features, and fluid parameters were coupled at the boundaries. An equation for the axial velocity component in the hot tube region was developed based on the characteristic that the axial velocity profiles under different conditions present similar patterns, the calculation method of reverse flow boundary which separates the working fluid into hot and cold fluids was described, and a set of relatively simple calculation methods for the internal flow field of vortex tubes was established based on the partition model. Three-dimensional velocity distributions inside the vortex tube under different working conditions were computed and analyzed. Further, the model was evaluated and validated through experimental data. The results showed good agreements of calculated data and experimental velocity fields. This work proposed a convenient calculation method for the estimation of the flow behavior inside a vortex tube and provide reliable predictions.